PERCEPTION AND UNDERSTANDING BY PUPILS LIFE MISTAKES OF LITERARY CHARACTERS AS A METHOD OF SELFIMPRUVEMENT - Buturlym, Tetiana (PSYCHOLOGICAL JOURNAL, 2017)
In the article the problem of necessity of awareness of character’s mistakes in fiction as a way to self-knowledge, self-perfection of a personality is actualized. It is marked importance to carry out the reflection of own actions, ideas, emotional states. A concept «error» is analysed. Classification of errors is resulted of S. Partiko: informative, modal, actual, temporal, local, situation, semiotics (vidobrazhuval’ni, value, tezaurusni), spriynyattevi, atenciyni, copy. Maintenance of concept «psychological error» is analysed (conscious or bezsvidomi ideas, senses, actions which violate a withstand harmonious connection with own «І» and world, predetermine deep heartfelt sufferings, internal). The examples are given from program works of Ukrainian literature of the 10th form: what exactly the characters did wrong, approximate ways of perfection of the behaviour are outlined. The mistakes of such works are analysed: Mariia and Omelko («Kaidash Family» by I. Nechui-Levytskyi), Chipka («Do oxen really roar, when mangers are full?» by Panas Myrnyi and Ivan Bilyk), Martyn («Martyn Borulia» by Ivan Karpenko-Karyi), Dokiia («Drudge» by В. Grinchenko), Moisei («Moisei» by I. Franko), Khoma («Jay’s wing» by I. Franko), protagonist («Intermezzo» by M. Kotsiubynskyi), Ivan («Shadows of forgotten ancestors» by M. Kotsiubynskyi), Sava («Earth» by O. Kobylianska), Ivan («Stone cross» by V. Stefanyk), Lukash («Forest song» by Lesia Ukrainka), protagonist («Moment» by V. Vynnychenko). It was defined how non-constructive character traits, behaviour, values affect life way of characters. Connection between possibility of a character and a student to make a step to self-development by awareness and correction of mistakes was found.